PENGEMBANGAN UNIT PRODUKSI SEKOLAH UNTUK MENINGKATKAN KUi'iLITAS SMK - Bada Haryadi (Jurnal Cakrawala Pendidikan, 2002)
The programs of vocational secondary school (SMK) arederived from the real requirement of employment Seriousattentions for productior! unit management are needed inrealizing such program and so are the participations of industgaland business. Production udit of vocational vocational secondaryschool is a business process conducted in school, which isprofit oriented in nature and the school members act as a player,optimizing resources of schools and its surroundings, into varietybusiness unit suitable to its capabilities and is managed professionally.By the professionalism of increasing production unit, thereare chances to improve the quality of vocational secondary schoolhigh school, educationally, economically, or socially In term ofeducation, students may irnbrove their knowledge. skills,organizing capabilities of business, practicing disciplines andinitiative, adding the study intensity, and be able to follow thescience and technological advancement; in term of economics,increasing the income and welfare, encourage decision taken uponeconomics consideration, increasing school's income for being more independent, increasing sources of facility maintenance cost,and increasing sources of school's operational cost; in term ofsocial, increasing the sense of togetherness -md responsibilities % .among all the school members in performing learning program,encourage business spirits to improve welfare, socializing schoolinto the community, business society, upon education operation,graduation, and business product.For production unit to run well, there are needed of ( I ) transparency,by which the participant will be attracted in productionunit activities. Transparency of financial in particular may leadto an honest behavior, admiration, and good examples; (2) fair in5 - distribution and working process by which all participant may , ,also be attracted in productjon unit activities; (3) power sharing,by which the working process should be accelerated by the handof expert; (4) risk taking, which is a consequence of performingproduction unit. Management may terminate the program whenthe risk is considered too much. To develop production unit thatlead to fill the requirement as complementary institution in fieldpractice of SMK students, its existence should be developed byfeasibility study and SWOT analyses.